CORRELATION BETWEEN PROTEIN INTAKE IN CHILDREN AGED 6-12 MONTHS AND PREVALENCE OF STUNTING: A LITERATURE REVIEW - Fatatul Anafah; Eko Winarti (Indonesian Health Literacy Journal, 2025)
Stunting is a significant public health issue characterized by chronic malnutrition, particularly during the first 1,000 days of life. This literature review investigates the correlation between protein intake in children aged 6–12 months and the prevalence of stunting. Utilizing a systematic review method following the PRISMA protocol, eight relevant articles published between 2020 and 2025 were analyzed. Findings consistently show that stunted children have lower overall protein and essential amino acid intake, particularly from animal sources, compared to their non-stunted peers. Inadequate dietary diversity, low family income, maternal education, and poor breastfeeding and complementary feeding practices emerged as key contributing factors to stunting. Despite abundant protein resources in some regions, cultural practices and limited nutritional knowledge often hinder adequate protein consumption. This review highlights the critical role of protein, especially animal-based protein, in preventing stunting and underscores the need for integrated strategies to improve dietary intake and socioeconomic conditions among vulnerable population.